1986
DOI: 10.2307/1590526
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Herpesvirus of Turkeys Replication Using Recombinant DNA

Abstract: DNA has been isolated from herpesvirus of turkeys (HVT) virions and used to construct a partial gene library in pBR-322. The recombinants have been characterized and shown to contain HVT DNA inserts. A representative recombinant containing a 5.9-kilobase HindIII fragment was used as a probe to quantitate the yields of HVT DNA in vitro and to follow the kinetics of viral DNA replication. The data shown that in chicken fibroblasts, viral DNA synthesis initiates by about 12-14 hr postinfection and that the yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These findings are supported by the fact that cloning in a plasmid/cosmid [9] as well as cosmid vector [17] resulted in the establishment of genomic libraries of HVT, not completely representing the BamHI-C fragment. Although HVT FC 126 is the strain of choice used for HVT cloning studies [4,9,14,17], the restriction site maps for PstI and BamHI shown in Fig. 1B significantly differ from those published by Igarashi et al [9] in number, size, and arrangement of the restriction fragments.…”
Section: Summary the Genomic Libraries Of The Herpesvirus Of Turkeysmentioning
confidence: 65%
“…These findings are supported by the fact that cloning in a plasmid/cosmid [9] as well as cosmid vector [17] resulted in the establishment of genomic libraries of HVT, not completely representing the BamHI-C fragment. Although HVT FC 126 is the strain of choice used for HVT cloning studies [4,9,14,17], the restriction site maps for PstI and BamHI shown in Fig. 1B significantly differ from those published by Igarashi et al [9] in number, size, and arrangement of the restriction fragments.…”
Section: Summary the Genomic Libraries Of The Herpesvirus Of Turkeysmentioning
confidence: 65%